Numerical investigation of steel reinforcement arrangement in reinforced concrete wall subjected to blast - Seman, M. A.; Sharifah Maszura, Syed Mohsin; Zaidi, A. M. A.; Jaini, Z. M. (IOP Publishing Ltd., 2021)
Three-dimensional (3D) numerical modelling of inverted-T shape reinforced concrete (RC) wall subjected to blast load is study in this paper. The walls have the same moment resistance with different steel reinforcement arrangements. It is subjected to 13.61 kg Trinitrotoluene (TNT) explosive at 1.21 m standoff distance from the centre. The Arbitrary Lagrange Euler (ALE) solvers coupling approach is employed for the interface analysis between air and structure to simulate the damage mechanism in AUTODYN numerical commercial software. The numerical damage indicator indicated, with mesh dependency assessment, the damage pattern vs experimental appeared precisely on the steel reinforcement grid due to the smaller element size compared to the coarse element used.